Improving the detectability of oxygen saturation level targets for preterm neonates: A laboratory test of tremolo and beacon sonifications. (September 2016) - Deschamps, Marie-Lys; Sanderson, Penelope; Hinckfuss, Kelly; Browning, Caitlin; Loeb, Robert G.; Liley, Helen; Liu, David
Abstract: Recent guidelines recommend oxygen saturation (SpO2 ) levels of 90%–95% for preterm neonates on supplemental oxygen but it is difficult to discern such levels with current pulse oximetry sonifications. We tested (1) whether adding levels of tremolo to a conventional log-linear pulse oximetry sonification would improve identification of SpO2 ranges, and (2) whether adding a beacon reference tone to conventional pulse oximetry confuses listeners about the direction of change. Participants using the Tremolo (94%) or Beacon (81%) sonifications identified SpO2 range significantly more accurately than participants using the LogLinear sonification (52%). The Beacon sonification did not confuse participants about direction of change. The Tremolo sonification may have advantages over the Beacon sonification for monitoring SpO2 of preterm neonates, but both must be further tested with clinicians in clinically representative scenarios, and with different levels of ambient noise and distractions. Highlights: Too much supplemental oxygen can be a hazard for some premature neonates. Pulse oximetry sonifications do not reveal when oxygen saturation is too high. We added tremolo or a reference beacon to the current pulse oximetry sonification. The Tremolo sonification supported better monitoring than the current sonification. The Beacon sonification supported better monitoring than the current sonification.